Influence of molecular weight on electrospinning of fiber materials obtained from solutions of polyacrylonitrile - T. H. Tenchurin; A. K. Budyka; V. A. Rykunov; A. D. Shepelev; V. R. Duflot (Тонкие химические технологии)
In the article influence of the molecular weight of polyacrylonitrile on electrospinning process and also on the diameter and mechanical properties of the obtained fibers and fiber materials are considered. Polymers with molecular weight from 280 000 to 700 000 were investigated. Fibers with a diameter from 200 to 1100 nm were obtained.